Emerging Roles of Microglia in Neuro-vascular Unit: Implications of Microglia-Neurons Interactions - Ding, Zhe; Guo, Shaohui; Luo, Lihui; Zheng, Yueying; Gan, Shuyuan; Kang, Xianhui; Wu, Xiaomin; Zhu, Shengmei (Frontiers in Cellular Neuroscience, 2021)
Microglia, which serve as the defensive interface of the nervous system, are activated in many neurological diseases. Their role as immune responding cells has been extensively studied in the past few years. Recent studies have demonstrated that neuronal feedback can be shaped by the molecular signals received and sent by microglia. Altered neuronal activity or synaptic plasticity leads to the release of various communication messages from neurons, which in turn exert effects on microglia. Research on microglia-neuron communication has thus expanded from focusing only on neurons to the neurovascular unit (NVU). This approach can be used to explore the potential mechanism of neurovascular coupling across sophisticated receptor systems and signaling cascades in health and disease. However, it remains unclear how microglia-neuron communication happens in the brain. Here, we discuss the functional contribution of microglia to synapses, neuroimmune communication, and neuronal activity. Moreover, the current state of knowledge of bidirectional control mechanisms regarding interactions between neurons and microglia are reviewed, with a focus on purinergic regulatory systems including ATP-P2RY12R signaling, ATP-adenosine-A1Rs/A2ARs, and the ATP-pannexin 1 hemichannel. This review aims to organize recent studies to highlight the multifunctional roles of microglia within the neural communication network in health and disease.